Exosome-based therapies for inflammatory disorders: a review of recent advances - Mavra Saleem; Khawar Ali Shahzad; Munazzah Marryum; Shekhar Singh; Quan Zhou; Siting Du; Shuanghu Wang; Chuxiao Shao; Imran Ibrahim Shaikh (Stem Cell Research & Therapy)
Abstract Exosomes, small extracellular vesicles secreted by cells, have emerged as focal mediators in intercellular communication and therapeutic interventions across diverse biomedical fields. Inflammatory disorders, including inflammatory bowel disease, acute liver injury, lung injury, neuroinflammation, and myocardial infarction, are complex conditions that require innovative therapeutic approaches. This review summarizes recent advances in exosome-based therapies for inflammatory disorders, highlighting their potential as diagnostic biomarkers and therapeutic agents. Exosomes have shown promise in reducing inflammation, promoting tissue repair, and improving functional outcomes in preclinical models of inflammatory disorders. However, further research is needed to overcome the challenges associated with exosome isolation, characterization, and delivery, as well as to fully understand their mechanisms of action. Current limitations and future directions in exosome research underscore the need for enhanced isolation techniques and deeper mechanistic insights to harness exosomes’ full therapeutic potential in clinical applications. Despite these challenges, exosome-based therapies hold great potential for the treatment of inflammatory disorders and may offer a new paradigm for personalized medication.